Comportamento do BRL-USD na vizinhança de vencimentos de derivativos de câmbio - Drevon, Philippe Fernandes (2016)
Several times a year, financial newspapers aficionados are used to read about the PTAX fixing in Brazil in the last day of the month. PTAX is the rate in which foreign exchange derivatives contracts index to in the country. This paper aims to establish if there is a direct influence between these contracts maturities and the price of the Brazilian currency vs. the U.S Dollar. We have run an OLS regression which captures a set of factors that have influenced prices at these exchanges since 2008 (for a total of 1890 data points). In addition to that, we have added a neighborhood dummy method for the derivatives maturities around which risk aversion was low. By doing that we have observed that the currency price is in fact affected by the maturities dates in periods of time in which market conditions allowed for liquid FX fixings, i.e. in months where the FX volatility was limited by low risk aversion. Finally, we found evidence of FX appreciation trends around these areas, fed by higher than usual demand for the brazilian currency by banks based in Brazil, buying mostly through futures derivatives. The short position in Real was held by foreign investor.